2020
DOI: 10.3892/ijmm.2020.4478
|View full text |Cite
|
Sign up to set email alerts
|

Role of the p53‑TRPM1/miR‑211‑MMP9 axis in UVB‑induced human melanocyte migration and its potential in repigmentation

Abstract: clinical studies have proven that ultraviolet B (UVB) based phototherapy can induce perifollicular and marginal repigmentation patterns in the skin of vitiligo patients. It is, however, difficult to conceive how melanocytes can easily exit from their tightly interconnected epidermal microenvironment to re-enter a different location in the skin to establish a new network with neighboring keratinocytes. While it is known that matrix metalloprotease 9 (MMP9) is involved in the degradation of the extracellular mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…Mutations in TRPM1 (Transient Receptor Potential Cation Channel Subfamily M Member 1) could induce complete congenital stationary night blindness [26]. UVB could affect the activity of the p53-TRPM1/miR-211-MMP9 axis in human melanocyte and induce melanocyte migration [27]. In this study, we also found that chi-miR-211 was highly expressed in cashmere goat skin in summer.…”
Section: Discussionsupporting
confidence: 55%
“…Mutations in TRPM1 (Transient Receptor Potential Cation Channel Subfamily M Member 1) could induce complete congenital stationary night blindness [26]. UVB could affect the activity of the p53-TRPM1/miR-211-MMP9 axis in human melanocyte and induce melanocyte migration [27]. In this study, we also found that chi-miR-211 was highly expressed in cashmere goat skin in summer.…”
Section: Discussionsupporting
confidence: 55%
“…Mutations in TRPM1 (Transient Receptor Potential Cation Channel Subfamily M Member 1) could induce complete congenital stationary night blindness [24]. UVB could affect the activity of the p53 TRPM1/miR 211 MMP9 axis in human melanocyte and induce melanocyte migration [25]. In this study, we also found that chi-miR-211 was highly expressed in cashmere goat skin in summer.…”
Section: Discussionsupporting
confidence: 55%
“…In this model, melanocytes that have acquired BRAF V600E would proliferate rapidly until the second pathway, and consequently MIR211-5p and MIR328-3p, is activated. MIR211-5p has previously been reported to be a transcriptionally regulated by both MITF (32), and UV exposure (56) . Future studies determining how these microRNAs are regulated in BRAF V600E nevus cells might identify additional therapeutic targets for nevus reduction or melanoma prevention.…”
Section: Discussionmentioning
confidence: 99%
“…PKC activation can also result in increased MAPK signaling 65,66 raising the possibility that internal MAPK fluctuations may play a role in toggling between BRAF V600E -induced proliferation versus arrest. MIR211-5p is also reported to be transcriptionally regulated by both MITF 67 and UV exposure 68 . Additionally, autocrine signaling might be at play, such that melanocyte density triggers the arrested state as predicted by recent mathematic modeling of nevus formation 8 .…”
Section: Discussionmentioning
confidence: 99%